The Specifics of Film or Reception of a Literary Ballad ("Wild Flowers" by F.A. Brabec) - Нікоряк, Наталія (PRAHA : VERBUM, 2022)
The objective of the article is to analyze the specifics of cinematic interpretation of the ballads from the collection “A Bouquet of Czech Folk Legends” (1853), written by a famous Czech writer and folklorist K.J. Erben, in the film by F.A. Brabec “Wild Flowers” (2000) within the concept of genre continuity. The cinematic text of the director F. Brabec fully preserves and conveys all the basic codes of the genre of literary ballad: the preciseness of the narrative, the depth of disclosure of life, the severity of the situations described, the limited personosphere, the dramatic and unexpected denouement. Therefore, the above texts are perceived as short “concentrated tragedies”. In addition, the director broadens the main text of the ballads, supplementing each plot with a backstory; he actively applies montage and film trails, as well as reduces time parameters, fragments and dialogues, at the same time preserving the main content of the original. Particular emphasis in the research has been laid on the fact that each ballad, reproduced by means of cinematic language (“Bouquet”, “The Water-Goblin”, “The Wedding Shirts”, “Lady Midday”, “The Golden Spinning Wheel”, “Daughter’s Curse”, “Christmas Eve”), is presented as a completed independent text and is regarded as an indispensable part of the holistic author’s concept.
Специфика кинорецепции литературной баллады («Букет» Ф.А. Брабеца)
Keywords: genre continuity; ballad; cinema ballad; “Wild Flowers”; K.J. Erben; F.A. Brabec